Analisis Awareness dan Willingness Generasi Milennial Terhadap Perilaku Membayar Zakat Penghasilan - Eki Muhammad Mulki Farhan; Zulkarnain Muhammad Ali; Rahmat Mulyana (Department Islamic Economics, 2024)
There is a huge potential zakat income in Indonesia. Millennial is one of the biggest income contributors. However, the zakat income collection is low. Therefore, it is important to analyze deeply the behavior of paying zakat income, especially in the millennial segment, on how to maximize the collectability of zakat income. The purpose of this study is to analyze the awareness and willingness of millennials towards the behavior of zakat income paying. The method of this research is quantitative method. The survey has been carried out by spreading online questionnaires for the millennials who are located in Jabodetabek city. The data collected was then analyzed using Structural Equation Modelling (SEM), Smart PLS ver. 3.29. In this study, we found that awareness influences the forming of willingness significantly, whereas willingness influences the behavior of paying zakat income among millennials. We also found that willingness plays role as a mediator between awareness and paying zakat income behavior. That means that we should pay more attention to the willingness, and how to turn the awareness into willingness before paying zakat income behavior. On the other hand, it was found that promotion also give a significant influence on willingness.